1971
DOI: 10.1136/jnnp.34.6.750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of median and ulnar sensory nerve action potentials in the diagnosis of the carpal tunnel syndrome

Abstract: SUMMARY Recording of median and ulnar digital sensory nerve action potentials in normal subjects showed that the ratio of the median (index finger) to ulnar (little finger) potential amplitude was consistently greater than one. In 15 patients with the carpal tunnel syndrome (seven bilateral) this ratio was found to be less than one for all but two of the 22 clinically affected hands, including three of the four hands with a normal motor latency to threshold stimulation and four of the five hands with a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…Motor conduction velocities in the ulnar nerve were not determined on all our patients, but in over half the patients with abnormal ulnar nerve sensory action potentials on whom motor conduction studies were carried out the lesion was found to be at the elbow. Loong and Seah (1971) have suggested that measurement of the ratio of median to ulnar nerve sensory action potential amplitude may be valuable in the diagnosis of carpal tunnel syndrome. Although an associated ulnar nerve lesion would not alter the validity of such a test, it may be expected to reduce its sensitivity.…”
Section: Carpal Tunnel Syndrome With Reduced Median Nerve Motor Condumentioning
confidence: 99%
“…Motor conduction velocities in the ulnar nerve were not determined on all our patients, but in over half the patients with abnormal ulnar nerve sensory action potentials on whom motor conduction studies were carried out the lesion was found to be at the elbow. Loong and Seah (1971) have suggested that measurement of the ratio of median to ulnar nerve sensory action potential amplitude may be valuable in the diagnosis of carpal tunnel syndrome. Although an associated ulnar nerve lesion would not alter the validity of such a test, it may be expected to reduce its sensitivity.…”
Section: Carpal Tunnel Syndrome With Reduced Median Nerve Motor Condumentioning
confidence: 99%
“…However, no study has been done up to this writing on CTS in paraplegic patients. We decided to study the ulnar nerve as well for comparison (Loong, 1971;Strephaniwsky, Bilowitt and Prasad, 1980).…”
mentioning
confidence: 99%
“…In view of the unusually large scatter of motor and sensory latency in normal median nerve (Hongell and Mattsson, 1971) we are presenting data on motor and sensory conduction 340 in a large group of normal subjects under standardized conditions. We have evaluated whether findings in median compared with those in ulnar nerve in the same patient allow mild or borderline cases of entrapment at the wrist to be recognized (Loong and Seah, 1971). 2.…”
mentioning
confidence: 99%